2019
DOI: 10.1002/cepa.1125
|View full text |Cite
|
Sign up to set email alerts
|

Flexural behaviour of engineered cementitious composite encased high strength steel composite beam

Abstract: In this paper, the flexural performance of a new type of composite beam comprised of High Strength Steel (HSS) section encased by polyvinyl alcohol-engineered cementitious composite (PVA-ECC) and lightweight concrete (LWC) is studied. An experimental investigation on the flexural performance of HSS beams encased by different thickness of ECC is conducted and their performances are compared with bare HSS beam and normal strength concrete (NSC) encased HSS beam. Four-point bending tests are carried out on simply… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…In contrast, recent studies by the authors [3][4][10][11][12] demonstrated that an alternative encasement configuration where the combined use of Engineered Cementitious Composites (ECC) and Light Weight Concrete (LWC) could successfully prevent local buckling and LTB of both NSS and HSS Ibeams. Since the material cost of ECC is higher than that of NC, ECC was only employed to encase the compression flange of the steel section to prevent the onset of local buckling and LTB, while LWC was employed in the remaining part of the beam to reduce the cost and weight of the beam.…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations
“…In contrast, recent studies by the authors [3][4][10][11][12] demonstrated that an alternative encasement configuration where the combined use of Engineered Cementitious Composites (ECC) and Light Weight Concrete (LWC) could successfully prevent local buckling and LTB of both NSS and HSS Ibeams. Since the material cost of ECC is higher than that of NC, ECC was only employed to encase the compression flange of the steel section to prevent the onset of local buckling and LTB, while LWC was employed in the remaining part of the beam to reduce the cost and weight of the beam.…”
Section: Introductionmentioning
confidence: 94%
“…1c) available in the FE package ABAQUS [13]. In order to reproduce the loading and support conditions used during the tests [4,[10][11][12], rigid loading and support plates were created and connected to the beam at the supports and loading points using the ABAQUS's tie constraint feature [13] (Fig. 1c).…”
Section: Key Features Of the 3d Nonlinear Fe Model Usedmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, there have been surprisingly limited research work and especially publications on composite beam combining HSS and ECC. The more recent publications are the experimental investigations carried out by Kabir et al [21,22] on compact and slender HSS beams encased with polyvinyl alcohol ECC (PVA-ECC) subjected to four-point bending. The authors found that a significant enhancement of flexural capacity and ductility were achieved for the HSS-ECC encased beam when compared with the bare HSS beam and the HSS-NSC encased beams tested.…”
Section: Introductionmentioning
confidence: 99%